2D and 3D simulation of geogrid-reinforced geocomposite material embankment on soft Bangkok clay. Issue 6 (1st December 2009) - Bergado, D.T.; Voottipruex, P.; Tanchaisawat, T.
Abstract : ABSTRACT: A full-scale test embankment, 6.0 m high, was constructed on soft Bangkok clay using a rubber tire chip–sand mixture as a geocomposite material reinforced with geogrid reinforcement with concrete block facing in the middle portion of the embankment. Silty sand backfill with rock-filled gabion facing were utilized at the sloping sides. The vertical and lateral deformations as well as excess pore pressures were monitored for 1 year. This study attempted to simulate the behavior of the full-scale test embankment by two-dimensional (2D) and three-dimensional (3D) numerical analyses. The 2D analysis was performed by PLAXIS software using undrained analysis in the construction stage and, thereafter, consolidation analysis was performed during the service stage. The 3D analysis was investigated by FLAC 3D software using the same constitutive models and properties of foundation soils as published by previous researchers. Owing to the use of geocomposite material as embankment materials, the observed values of the vertical and horizontal deformations, excess pore pressures, and the reinforcement tensions were quite low. Thus, there were no significant differences between the 2D and 3D simulated results in comparison with the corresponding measurements of embankment behavior. As expected, however, the 3D predictions were slightly lower than the corresponding values from the 2D predictions. Consequently, the lower 3D predicted values of vertical and lateral deformations, excess pore pressures and reinforcement tensions in comparison with the 2D predictions were quite consistent and reasonable.